PENGARUH PENGGUNAAN JENIS GULA TERHADAP MUTU KURMA TOMAT: (The effect of different sugar type on the quality of tomato date) - Amran Laga; Jumriah Langkong; Muhpidah Muhpidah (jurnal1, 2019)
The processing of tomatoes into the product was able to maintain the storability and also increased the economic value of fresh tomatoes. Different types of sugar gave different results for the quality and the panelist preference of tomatoe dates. The analysis of water content showed that the use of sugar had the lowest moisture content of 13.8%, acidity level of 5.31 and was able to maintain a level of vitamin C after processing of 60.25%. While the use of brown sugar in tomato dates Showed moisture content of 14.8%, acidity level of 5.84 and only able to maintain vitamin C levels after processing of 37.82%. The panelist preference showed that tomato dated with sugar was more preferred than tomato date s with brown sugar